Efficient generation, distribution, and feedback loop of worker information in the assembly Effiziente erstellung, distribution und Rückmeldung von werkerinformationen in der montage - Franke, Jörg; Risch, Florian (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2009)
In manual assembly workplaces for customized and complex products with short product life cycles, the assembly workers - who are the creative basis of the companies' performance - have to be supported to cope with the rising requirements. For this purpose the Institute for Manufacturing Automation and Production Systems (FAPS) of the University of Erlangen-Nuremberg considers the generation, distribution, and feedback loop of information in the assembly based on an integrated systems approach. In doing so, the developed worker information systems can play a major role in handling the complexity of production. They offer support for a self dependent and flexible processing of orders by providing an educationally and psychologically prepared presentation of information. Through this, they contribute to minimize set-up times, effectively communicate technical changes, and quickly carry out learning curve effects.
CRIS-Team Scopus Importer:2024-08-06